Growth of giant tiger prawn, Penaeus monodon Fabricius, under co-culture with a discarded filamentous seaweed, Chaetomorpha ligustica (Kützing) Kützing, at an aquarium-scale - Tsutsui, Isao; Kanjanaworakul, Poonmanee; Srisapoome, Prapansak; Aue-umneoy, Dusit; Hamano, Kaoru (My University, 2010)
Growth of juvenile giant tiger prawn, Penaeus monodon Fabricius, was evaluated at an aquarium-scale in co-culture with a discarded filamentous seaweed, Chaetomorpha ligustica (Kützing) Kützing. Juveniles at different ages in days were examined, designated as J 16, J 44, J 58, J 93 and J 128, where a 1-day-old juvenile (J 1) is equivalent to a 20-day-old post-larva (PL 20)). Juveniles at every age group grazed directly on live C. ligustica, even those fed an artificial shrimp diet to satiation. Mean specific growth rate (SGR: % day-1) was higher in early age juveniles. Compared to mono-culture, significant differences in growth were observed at J 16 (4.44% day-1) and J 44 (1.60% day-1); however, no significant differences were recorded at J 58 (1.16% day-1), J 93 (0.75% day-1) or J 128 (0.45% day-1). It was concluded that co-culture of giant tiger prawn with C. ligustica has a dietary advantage, especially in early age juveniles. © 2009 Springer Science+Business Media B.V.
Keywords: Chaetomorpha ligustica; Co-culture; Discarded filamentous seaweed; Giant tiger prawn; Growth enhancement; Penaeus monodon